Socio-Personal and Socio-Economic Profile of Goat Owners in India - Roy, Rakesh; Tiwari, Rupasi (Indian Journal of Extension Education, 2016)
The study was carried out with the objective to determine the socio-economic characteristic of the goat owners of India.  The study was purposively conducted in the state of West Bengal and Uttar Pradesh due to its high goat population. The  socio-personal study shows that the mean age of the goat owners was around 41 years; they were mostly illiterates with  medium family education status, low social participation but had high experience in goat farming. Agriculture was the  main occupation of the goat owners; annual family income was about 0.77 lakhs where in 0.16 lakhs came from goat  farming. Average flock size was about 18 goats and they mainly reared it for meat purpose but there was big difference in  flock size between the two states. The goat owners possess negligible numbers of other large animals too.
Keywords: Socio-personal profile; socio-economic profile; goat owners